LAGEYAN BAWOR DALAM CERITA “BAWOR DADI RATU” SEBAGAI PENDEKATAN PENDAMPINGAN BERBASIS BUDAYA DI ERA GLOBAL - Renoardi, Amos; Engel, Jacob Daan; Suwarto, Suwarto (Universitas Lancang Kuning, 2024)
This research aims to produce effective culture-based mentoring principles to preserve the value of local wisdom and ethical education in the Banyumasan Javanese community. This research was motivated by the fact that cultural values have been displaced in the modern era while recognizing the importance of exploring the local wisdom of Pakeliran Banyumasan as a value that needs to be explored and preserved. This research uses a qualitative method with an ethnographic approach. Observation, interviews, and documentation were used to collect data in this study, so that the principles of culture-based mentoring based on Bawor's lageyan in the story